Pseudobiceros wirtzi sp. nov. (Polycladida: Cotylea) from Senegal with revision of valid species of the genus - Bahia, Juliana; Schrödl, Michael (Zootaxa, 2016)
The genus Pseudobiceros was established based on the presence of two male gonopores, duplicated male reproductive structures, smooth dorsal surface, complex folded pseudotentacles, and simple ruffled pharynx. We describe here a new species of Pseudobiceros from the African continent that has been repeatedly reported and photographed over the years, but lacked a formal description. Pseudobiceros wirtzi sp. nov. is described based on morphological and histological characters. Our bibliographical revision of the genus considers 39 species to be valid. We applied the diagnostic characters of Pseudobiceros to Pseudoceros species listed before the split between these genera, and to species listed as incertae sedis. Pseudobiceros punctatus (Laidlaw 1902) nov. comb. shows typical features of Pseudobiceros. We also discuss other species with historically conflictive generic placements or problematic synonymy and summarize distributions and species characteristics in a comparative table. Most Pseudobiceros species still need re-descriptions to fill gaps regarding internal and pharynx details. Further sampling on the Eastern Africa coast and on mid-Atlantic Islands should prove useful in getting a general view of polyclad biodiversity and biogeography in the Tropical and South Atlantic.